Lateral manual asymmetries: A longitudinal study from birth to 24 months. Issue 1 (20th November 2012) - Jacobsohn, Lia; Rodrigues, Paula; Vasconcelos, Olga; Corbetta, Daniela; Barreiros, Joao
Abstract Longitudinal studies tracking the early development of manual asymmetries are fairly rare compared to the large number of studies assessing hand preference in infancy. Moreover, most prior longitudinal studies have performed behavioral observation over relatively short‐time spans considering the celerity of early development. This study aims (i) to investigate the direction and consistency of manual lateral asymmetries over a longer period, from birth to 24 months of age, and (ii) to compare individual and group trajectories to better understand discrepancies between prior studies. Nineteen healthy infants were observed eight times in tasks that were adjusted progressively as infants manual skills developed. Results suggested two distinct periods in terms of the direction, strength, and consistency of manual preference. First, infants went through an initial phase characterized by a lack of lateral manual asymmetries. From 9 months of age, however, group analyses revealed an emerging and steadily growing right lateral bias over time, while individual trajectories revealed that the group‐level right‐bias formed progressively from a background of highly fluctuating and highly variable developmental trajectories. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 56: 58–72, 2014.